Efficient activation of ferrate(VI) by colloid manganese dioxide: Comprehensive elucidation of the surface-promoted mechanism - Mengfan Luo; Heng Zhang; Peng Zhou; Zhaokun Xiong; Bingkun Huang; Jiali Peng; Liu, Rui; Liu, Wen; Bo Lai (Water Research, 2022)
Current research focuses on introducing additional energy or reducing agents to directly accelerate the formation of Fe(IV) and Fe(V) from ferrate (Fe(VI)), thereby ameliorating the oxidation activity of Fe(VI). Interestingly, this study discovers that colloid manganese dioxide (cMnO2) can remarkably promote Fe(VI) to remove various contaminants via a novel surface-promoted pathway. Many lines of evidence suggest that high-valent Fe species are the primary active oxidants in the cMnO2−Fe(VI) system, however, the underlying activation mechanism for the direct reduction of Fe(VI) by cMnO2 to generate Fe(IV)/Fe(V) is eliminated. Further analysis found that Fe(VI) can combine with the vacancies in cMnO2 to form precursor complex (cMnO2−Fe(VI)*), which possesses a higher oxidation potential than Fe(VI). This makes cMnO2−Fe(VI)* is more vigorous to oxidize pollutants with electron-rich moieties through the electron transfer step than alone Fe(VI), resulting in producing Fe(V) and Fe(IV). The products of Fe(VI) decay (i.e., Fe(II), Fe(III), and H2O2) are revealed to play vital roles in further boosting the formation of Fe(IV) and Fe(V). Most importantly, the catalytic stability of cMnO2 in complicated waters is superior to popular reductants, suggesting its outstanding application potential. Taken together, this work provides a full-scale insight into the surface-promoted mechanism in Fe(VI) oxidation process, thus providing an efficient and green strategy for Fe(VI) activation.
Keywords: Colloid manganese dioxide; Ferrate; oxidation; Sulfamethoxazole; Surface-promoted